Construction of a Stable and Temperature-Responsive Yeast Cell Factory for Crocetin Biosynthesis Using CRISPR-Cas9 - Liu, Tengfei; Dong, Chang; Qi, Mingming; Zhang, Bei; Huang, Lei; Xu, Zhinan; Lian, Jiazhang (Frontiers in Bioengineering and Biotechnology, 2020)
Crocetin is a plant natural product with broad medicinal applications, such as improvement of sleep quality and attenuation of physical fatigue. However, crocetin production using microbial cell factories is still far from satisfaction, probably due to the conflict between cell growth and product accumulation. In the present work, a temperature-responsive crocetin-producing Saccharomyces cerevisiae strain was established to coordinate cell growth, precursor (zeaxanthin) generation, and product (crocetin) biosynthesis. The production of crocetin was further enhanced via increasing the copy numbers of CCD2 and ALDH genes using the CRISPR-Cas9 based multiplex genome integration technology. The final engineered strain TL009 produced crocetin up to 139.67 ±2.24 μg/g DCW. The advantage of the temperature switch based crocetin production was particularly demonstrated by much higher zeaxanthin conversion yield. This study highlights the potential of the temperature-responsive yeast platform strains to increase the production of other valuable carotenoid derivatives.